2009
DOI: 10.1017/s2040174409990183
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in aging rats due to low-protein diet during mid-gestation

Abstract: Nephrogenesis in the rat starts mid-gestation and continues into lactation. Maternal low protein (LP) intake leads to renal injury in rats and associates with mild renal injury in humans. We hypothesized that LP during early nephrogenesis or throughout gestation would induce more renal injury in rat offspring than when LP was only present before nephrogenesis. Pregnant rats were fed LP diet (9% casein) at early gestation (LPE, day 0-7), mid (LPM, day 8-14), late (LPL, day 15-22) or throughout gestation (LPA, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Maternal protein restriction in rodent pregnancy is well established as a driver of metabolic and cardiovascular impairments in the resulting offspring as they age (Petry et al 2001; Bellinger et al 2006; Erhuma et al 2007 b ; Joles et al 2010). This nutritional programming of adult function is generally associated with evidence of altered, but not always impaired, fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal protein restriction in rodent pregnancy is well established as a driver of metabolic and cardiovascular impairments in the resulting offspring as they age (Petry et al 2001; Bellinger et al 2006; Erhuma et al 2007 b ; Joles et al 2010). This nutritional programming of adult function is generally associated with evidence of altered, but not always impaired, fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of maternal protein restriction on organ structure can be clearly related to functional outcomes. Offspring from protein-restricted animals are hypertensive and develop proteinuria (Joles et al 2010) with ageing and are glucose intolerant (Petry et al 2001).…”
mentioning
confidence: 99%
“…Rats at 5 weeks, 10 weeks, and 6 months of age were housed in metabolic cages for 24 hours and urine collected as previously described [21]. Urine concentrations of adrenaline, noradrenaline, and dopamine were determined using the DLD Diagnostika catecholamine ELISA kit (DLD Diagnostika GmbH, Hamburg, Germany), following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies by Woods et al also demonstrated that a moderate reduction in maternal protein during gestation did not alter BP in female low protein offspring [6]. Joles et al reported that, fetal exposure to low protein during gestation increased renal injury in the aging male kidney [81] (Figure 3). Yet, an additional study indicated that female offspring exposed to moderate maternal protein restriction during fetal life were protected against the accelerated development of renal injury [79].…”
Section: Introductionmentioning
confidence: 99%